Determination of Ethylmalonic Acid in Human Urine by Ion Chromatography with Suppressed Conductivity - Destanoğlu, Orhan; Cansever, Mehmet Şerif; Yılmaz, Gülçin Gümüş (Orbital: The Electronic Journal of Chemistry, 2015)
We present here a new method for the determination of EMA in urine by ion chromatography (IC) with suppressed conductivity detection. The separations on an anion exchange column have been accomplished with an optimized multi-step gradient eluent program (5 mM for 0-7 min, 5-50 mM from 7 to 30 min, 50 mM for 30-40 min, 50-5 mM from 40 to 45 min, 5mM for 45-50 min at flow-rate 0.2 mL/min) using NaOH as the eluent. The temperatures of both the column and suppressed conductivity detector were 40 °C. The suppressor current was 25 mA. The injection loop volume was 100 µL. Prior to injection, a clean-up procedure has been applied to urine samples for sulfate removal using BaCl2 precipitation followed by elimination of cationic and some organic compounds using strongly acid cation-exchange resin and C18 solid phase extraction cartridge, respectively. Concentration range of EMA for linear external calibration curve was between 0.202 -30.278 µmol/L (r2=0.999). The limit of detection and the limit of quantitation were 61 nmol/L and 202 nmol/L based on the signal-to-noise ratio equal to 3 and 10, respectively. The average recoveries of EMA for normal urine samples were between 98.2-99.3 % with less than 1.1 % relative standard deviation (RSD), and for pathological sample were between 97.2-107.8% with less than 1.9% RSD in both intra-day and inter-day assays. The average concentrations of EMA normalized against creatinine for healthy human urine samples and a pathological sample were 1.14 (0.88-1.50) and 128.95 (128.04-129.33) µmol mmol-1 creatinine, respectively.DOI:  http://dx.doi.org/10.17807/orbital.v7i2.574